Rethinking the position of ethnic Chinese Indonesians - Wu, L.C. (2016)
This article examines the position of ethnic Chinese Indonesians from the Dutch colonial period to the post-Suharto era and analyses the factors that shaped their position. This article will focus on the' position of ethnic Chinese Indonesians in the aspects of economy, sociocultural sphere and politics. Under Dutch colonial rule, which began in the seventeenth century, the colonial regime enforced the divide-and-rule policy that deterred the interactions between the Chinese and the indigenous population. The Dutch allowed the Chinese to form ethnic-based organisations, establish Chinese-language presses and open Chinese-medium schools as they wanted the Chinese to maintain their "Chinese-ness" in order to keep them as a distinct ethnic group. Moreover, the Dutch used the Chinese instead of the indigenous " - population to fill most economic niches in order to prevent the rise of an indigenous merchant class that might challenge their position. This had further widened the economic disparity between the Chinese and the indigenous people. During the Sukarno years (1950-1965), the Chinese continued to enjoy freedom to establish and operate Chinese organisations, Chineselanguage presses and Chinese-medium schools because Sukarno was close to China and hence was relatively tole;ant to the Chinese in Indonesia. The Chinese were also allowed to actively getting involved in politics. However, the Sukarno regime introduced a few discriminatory policies to reduce Chinese economic interests and assist indigenous businesspeople. During the Suharto's rule (1966-1998), due to the anti-communist politics associated with the Cold War, the Suharto regime perceived the ethnic Chinese as the potential 'fifth column' for China and introduced forced assimilation policies to curtail Chinese culture as well as control the Chinese. The Chinese were also discouraged from actively getting involved in politics and were only given opportunities to get involved in business activities. In the post-Suharto era (1998-present), the position of ethnic Chinese Indonesians has improved considerably as they are now allowed to openly express their ethnic and cultural identities as well as actively participate in politics. This article argues that the reversal of attitudes toward the Chinese was catalysed by capital flight and the 'exodus' of Chinese after the anti-Chinese riots in May 1998. It was also due to the rise of political leaders who were open-minded and sympathetic to the situation of the Chinese such as former presidents Abdurrahman Wahid and Megawati Sukarnoputri. Besides that, the rise of China as an economic power also indirectly changed the attitude of post-Suharto governments towards Chinese Indonesians. This article concludes that the position of ethnic Chinese Indonesians was shaped by not only the interests and agendas of the power-holders but also the anti-communist politics associated with the Cold War, the rise of open-minded Indonesian political leaders, Indonesia-China relations and the globalisation of the economic position of China.